Impediments of environment management system (EMS) implementation in Malaysian local authorities – a preliminary finding - Madi, Nero; Joseph, Corina; Rahmat, Mariam (2017)
The implementation of environmental management system (EMS) by public sector agencies is in line with the Malaysian Government Transformation Programme (GTP) and the New Public Management doctrine. Local authority is chosen as a sample because of its important role in advancing towards sustainable development.This study aims to examine impediments to the ISO 14001 implementation by Malaysian local authorities using the institutional theory as the underlying framework. The survey instrument was developed and distributed via mail to all 146 local authorities in Malaysia.Finding revealed that the impediments to the EMS implementation were explained by lack of coercive, normative and mimetic isomorphism under the institutional theory.It is expected that the survey findings would fill in the gaps in the literature in better understanding the lack of implementation of IS00 14001 particularly in the emerging economy.